2023
DOI: 10.1101/2023.04.28.538696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The duplication of genomes and gene regulatory networks and its potential for evolutionary adaptation and survival

Abstract: The importance of whole genome duplication (WGD), or polyploidy, for evolution, is controversial. Whereas some view WGD mainly as detrimental and an evolutionary dead end, there is growing evidence that (the establishment of) polyploidy can help overcome environmental change, stressful conditions, or periods of extinction. However, despite much research, the mechanistic underpinnings of why and how polyploids might be able to outcompete or outlive non-polyploids at times of environmental upheaval remain elusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Selmecki et al (2015) revealed an increase in genetic variation and a higher adaptation rate in tetraploid compared to haploid and diploid yeast. Third, an increased complexity from doubled and/or merged gene regulatory networks (GRN) is expected to enable more extreme phenotypes (Yao et al 2019, Ebadi et al 2023. This increased GRN complexity can therefore be regarded as a genomewide effect that enables larger phenotypic changes from mutations, possibly beneficial under extreme environmental change (Yao et al 2019).…”
Section: Delayed Fitness Dynamics: Evolution and Changes In Adaptive ...mentioning
confidence: 99%
“…Selmecki et al (2015) revealed an increase in genetic variation and a higher adaptation rate in tetraploid compared to haploid and diploid yeast. Third, an increased complexity from doubled and/or merged gene regulatory networks (GRN) is expected to enable more extreme phenotypes (Yao et al 2019, Ebadi et al 2023. This increased GRN complexity can therefore be regarded as a genomewide effect that enables larger phenotypic changes from mutations, possibly beneficial under extreme environmental change (Yao et al 2019).…”
Section: Delayed Fitness Dynamics: Evolution and Changes In Adaptive ...mentioning
confidence: 99%